Analisis Kepuasan Wisatawan Terkait Destinasi Wisata di Pantai Selong Belanak (Portal ABDIMAS, 2023)
Selong Belanak Beach is one of the beaches that is quite famous, especially for its beauty and beauty. Its strategic location, famous history, public facilities and extras, make Selong Belanak beach a very attractive location for tourists. But one of the important roles for these tourist destinations is the cleanliness of the beach itself, providing comfort for tourists. Direct observation study and descriptive cross-sectional study with a random survey of 54 local and foreign tourists about the cleanliness of Selong Belanak beach. Through a survey, we collect tourists' evaluations of the current sanitation of public facilities (toilets, parking and rest areas), additional facilities (restaurants, gift shops and street vendors), and the condition of MCK facilities (trash bins) at Selong Belanak Beach, giving a score very satisfied, satisfied, moderately satisfied, dissatisfied, very dissatisfied. Through direct observation we saw physical objects around the environment such as geography and the facilities available at Selong Belanak beach which were collected through interviews with local informants. Respondents as a whole showed a positive response "quite satisfied" 14 respondents, and 3 foreign respondents regarding the quality of Selong Belanak beach sanitation. Public facilities and additional facilities are generally considered quite clean by all respondents. But the opinions of tourists point to the â€œinsufficientâ€ availability of waste. Public facilities 4 public toilets, 2 parking lots, push bins, other results that are considered poor or below expectations regarding certain public facilities must be taken care of to provide a better tourist attraction. Cleanliness is a tourist attraction itself, therefore maintaining cleanliness is important for the success of tourism.
Keywords: environmental sanitation, public and additional facilities, tourists.